2021
DOI: 10.3390/ijms22052245
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cardiomyocyte Oxidative Stress Leads to Bystander Senescence of Cardiac Stromal Cells

Abstract: Accumulation of senescent cells in tissues during normal or accelerated aging has been shown to be detrimental and to favor the outcomes of age-related diseases such as heart failure (HF). We have previously shown that oxidative stress dependent on monoamine oxidase A (MAOA) activity in cardiomyocytes promotes mitochondrial damage, the formation of telomere-associated foci, senescence markers, and triggers systolic cardiac dysfunction in a model of transgenic mice overexpressing MAOA in cardiomyocytes (Tg MAOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…231 In addition, several reports have suggested that oxidative stress in cardiomyocytes induces the premature senescence of cardiac stromal cells, increases the recruitment of CCR 2+ monocytes, and eventually contributes to an excessive inflammatory response and cardiac dysfunction. 232 Moreover, several studies have shown that aging-related increases in ROS levels contribute to mitochondrial dysfunction, metabolic imbalance and irreparable cardiomyocyte damage via accumulation of mtDNA damage and mutations, which could lead to HF.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…231 In addition, several reports have suggested that oxidative stress in cardiomyocytes induces the premature senescence of cardiac stromal cells, increases the recruitment of CCR 2+ monocytes, and eventually contributes to an excessive inflammatory response and cardiac dysfunction. 232 Moreover, several studies have shown that aging-related increases in ROS levels contribute to mitochondrial dysfunction, metabolic imbalance and irreparable cardiomyocyte damage via accumulation of mtDNA damage and mutations, which could lead to HF.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…Cardiomyocytes from TgMAO‐A mice show increased telomere dysfunction and markers of cellular senescence, which can be rescued by treatment with antioxidant N‐acetyl cysteine (NAC) [9]. More recently, it was shown that MAO‐A driven cardiomyocyte senescence also induces paracrine senescence to cardiac stromal cells [95].…”
Section: Mitochondria As Inducers Of Senescencementioning
confidence: 99%
“…The importance of MAO for left ventricular remodeling and heart failure development can be shown in mice with chronic overexpression of MAO-A. Here, reactive oxygen species [ 136 ] and 4-hydroxynonenal concentrations increase, followed by mitochondrial dysfunction [ 181 ], cardiomyocyte hypertrophy, reduced left ventricular function and increased cardiac fibrosis [ 73 ], as well as increased cardiac inflammation [ 182 ] (for review, see [ 134 , 183 ]). When transgenic animals are treated with the antioxidant N-acetyl cysteine part of the above effects can be rescued [ 136 , 184 ].…”
Section: Monoamine Oxidases (Mao)mentioning
confidence: 99%